(3eXgQ GdJHLjd dbhd MSHj Gddg hfYe Gdhcjds - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3hHO agPG JYdjb SejJg eXgQ GdJHLjd dbhd MSHj Gddg hfYe Gdhcjd s
(3BNQgG (B:s
(3ef jCNP GdMb hjTaj GdZdjd , EPG JhcdfG Ydjg caG aMSHfG Gddg hfYe Gdhcjd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI s
Keywords: (3GdJUha hGdBOGH GdTQYjIs